Lexical Metaphor in Bon Jovi’s Selected Songs - Rosni L Pasaribu; Siti Aisah Ginting (LINGUISTICA, 2013)
ABSTRACT   This  thesis  deals  with  Lexical  Metaphor  as  found  in  the  Selected  Songs  of  Bon Jovi.  It  was  conducted  to  discover  the  types  of  Lexical  of  Metaphor  as  proposed  by Saragih  (2006:162)  namely  Lexical  metaphor  that  is  formed  by  comparing  Noun  with Noun, Lexical metaphor that is formed by comparing Noun with  verb, Lexical metaphor that  is  formed  by  comparing  Noun  with  Adjective,  Lexical  metaphor  that  is  comparing two ideologys or concepts, as symbol of sound. In this researh the writer found out three types  of  lexical  metaphor  that  applied  in  the  Bon  Jovi’s  songs.  The  research  was conducted  by  using  descriptive  qualitative  approach.  The  subjects  of  the  study  is  all contetnts of the selected songs of Bon Jovi’s song.   The  findings  indicate  that  lexical  metaphor  found  in  the  song  include,  Nominal-Verbal/Verbal-Nominal  (61%),Nominal-Nominal  (16%),Nominal-Adjective  (13%). Lexical metaphor formed by comparing Noun with Verb was the most dominatly \ in Bon Jovi’s Selected songs. Because he described the meaning and represented his feelings.  Keywords : Lexical Metaphor, Bon Jovi’s Selected Songs